Effect of Blade Diameter on the Performance of Horizontal-Axis Ocean Current Turbine - Mansoor Ahmed Zaib; Arbaz Waqar; Shoukat Abbas; Saeed Badshah; Sajjad Ahmad; Muhammad Amjad; Seyed Saeid Rahimian Koloor; Mohamed Eldessouki (Energies, 2022)
The horizontal-axis ocean current turbine under investigation is a three-blade rotor that uses the flow of water to rotate its blade. The mechanical energy of a turbine is converted into electrical energy using a generator. The horizontal-axis ocean current turbine provides a nongrid robust and sustainable power source. In this study, the blade design is optimized to achieve higher efficiency, as the blade design of the hydrokinetic turbine has a considerable effect on its output efficiency. All the simulations of this turbine are performed on ANSYS software, based on the Reynolds Averaged Navier–Stokes (RANS) equations. Three-dimensional (CFD) simulations are then performed to evaluate the performance of the rotor at a steady state. To examine the turbine’s efficiency, the inner diameter of the rotor is varied in all three cases. The attained result concludes that the highest Cm value is about 0.24 J at a tip-speed ratio (TSR) of 0.8 at a constant speed of 0.7 m/s. From 1 TSR onward, a further decrease occurs in the power coefficient. That point indicates the optimum velocity at which maximum power exists. The pressure contour shows that maximum dynamic pressure exists at the convex side of the advancing blade. The value obtained at that place is −348 Pa for case 1. When the dynamic pressure increases, the power also increases. The same trend is observed for case 2 and case 3, with the same value of optimum TSR = 0.8.